Psychometric validation of the EuroQoL 5-Dimension 5-Level (EQ-5D-5L) in Chinese patients with adolescent idiopathic scoliosis. Issue 1 (December 2016) - Cheung, Prudence; Wong, Carlos; Samartzis, Dino; Luk, Keith; Lam, Cindy; Cheung, Kenneth; Cheung, Jason
Abstract Background Scoliosis is a common spinal deformity that occurs often during adolescence. Previous studies suggested that adolescent idiopathic scoliosis (AIS) patients can have various aspects of their lives being affected, due to disease presentation and/or treatment received. It is important to define a reliable instrument based on which the affected patients' health-related quality of life can be assessed. This study aims to assess the validity, reliability and sensitivity of the EuroQoL 5-dimension 5-level (EQ-5D-5L) in Chinese patients with AIS. Methods Adolescent idiopathic scoliosis patients of Chinese descent were prospectively recruited to complete both the traditional Chinese versions of the EQ-5D-5L and the refined Scoliosis Research Society-22 (SRS-22r) questionnaires. Patients' demographic profiles and corresponding clinical parameters including treatment modalities, spinal curve pattern and magnitude, and duration of bracing were recorded. Telephone interviews were then conducted at least two weeks later for the assessment of test-retest reliability. Statistical analysis was performed: construct validity of the EQ-5D-5L domains were assessed using Spearman's correlation test against the SRS-22r; whereas intra-class correlation coefficient (ICC) was used to assess the test-retest reliability, and agreement over the test-retest period was expressed in percentages. Also, the sensitivity of the EQ-5D-5L in differentiating various clinical known groups was determined by effect size, independent t-test and analysis of variance. Results A total of 227 AIS patients were recruited. Scores of domains of the EQ-5D-5L correlated significantly (r: 0.57-0.74) with the scores of the SRS-22r domains that were intended to measure similar constructs, supporting construct validity. The EQ-5D-5L domain responses and utility scores showed good test-retest reliability (ICC: 0.777; agreement: 76.4 -98.1 %). Internal consistency was good (Cronbach's α: 0.78) for the EQ-5D-5L utility score. The EQ-5D-5L utility score was sensitive in detecting differences between subjects who had different treatment modalities and bracing duration, but not for curve pattern and its magnitude. Conclusions The EQ-5D-5L is found to be a valid, reliable and sensitive measure to assess the health-related quality of life in Chinese AIS patients. This potentiates the possibility of utilizing the EQ-5D-5L to estimate AIS patients' health-related quality of life, based on which the outcome of various treatment options can eventually be evaluated.